1989
DOI: 10.1055/s-2008-1043256
|View full text |Cite
|
Sign up to set email alerts
|

Y-Ureterokutaneostomie bei angeborenem Hydroureter - eine kausale Therapie?

Abstract: Between 1975 and 1987 30 patients with congenital hydronephrosis and megaureter were treated by Y-cutaneostomy according to Sober. 28 are still under our control. 5 of them showed normalisation of urine drainage. No further operation except the closure of the stoma was necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Primary functional obstructed megaureter may be an adynamic juxtavesical segment which tends to improve spontaneously (Scholtmeijer, 1989). Like Keating et al (1989) and Jenny et al (1989), we found that many antenatal and neonatal ureteric dilatations at the level of the vesicoureteric junction improved with time. Similar findings were reported >25 years ago (Olbing and Mellin, 1966).…”
Section: Discussionmentioning
confidence: 61%
“…Primary functional obstructed megaureter may be an adynamic juxtavesical segment which tends to improve spontaneously (Scholtmeijer, 1989). Like Keating et al (1989) and Jenny et al (1989), we found that many antenatal and neonatal ureteric dilatations at the level of the vesicoureteric junction improved with time. Similar findings were reported >25 years ago (Olbing and Mellin, 1966).…”
Section: Discussionmentioning
confidence: 61%